A construção discursiva das identidades peruana e venezuelana no contexto de um “comunismo” virtual no Peru - Taipe Rivas, Milagro del Pilar (2024)
This article analyzes the identity constructions of Peruvians and Venezuelans that emerged in the context prior to the 2021 presidential runoff held in Peru. The main objective is to identify the positionings and identities that circulated within and between both groups through their written discourses, as well as to determine their underlying reasons and purposes. To this end, Bucholtz and Hall’s approach (2005) on identity as an intrinsically relational phenomenon constructed and changed in linguistic practice is adopted. The data was obtained by applying the technique of peripheral observation on the social network Twitter, from which 10 tweets were selected that deal with the large number of Venezuelan immigrants in Peru and/or the prospective “communism” that was speculated in that country in view of Pedro Castillo’s victory in the 2021 first ballot. The main results identified are the following: the anticommunist profile of brave Peruvian and Venezuelan immigrants who saw the left-wing option as a danger to the common good (and thus encouraged its massive rejection); as well as the communist identity of Peruvians positioned as ignorant, who, by disapproving of the right-wing and choosing change, implicitly promoted the vote for Castillo.